Understanding the impact of pandemics on society with a special focus on COVID‐19. (11th December 2022) - Malik, Sahil; Chhabra, Meghna; Chandra, Geetika Malik
Abstract: The study aims to ascertain how different levels of society have been influenced by the impact of pandemics over the last many years. The study also determines the societal implications of the COVID‐19 pandemic. The integrative literature survey method is adopted to extract the secondary data pertinent to the socio‐economic effect of pandemics and COVID‐19 on society. Primary data is collected to diagnose the impact of the COVID‐19 pandemic and lockdown on employees ( N = 210) working in the Indian organized sector. Findings of the study suggest that pandemics have been a cause of economic slowdown measured with a fall in gross domestic product (GDP) at the macro level. The reduced level of economic activity is found to be negatively related to an individual socio‐economic status building their psychological distress. The descriptive analysis of the data reveals that although employees have managed their jobs and finances during COVID‐19, they have experienced stress in their lives due to the pandemic. The study assimilates the pandemic effect using inductive reasoning to develop a COVID quadrilateral conceptual framework.